Abciximab reduces mortality in diabetics following percutaneous coronary intervention - Bhatt, Deepak L; Marso, Steven P; Lincoff, A.Michael; Wolski, Katherine E; Ellis, Stephen G; Topol, Eric J (Journal of the American College of Cardiology, 2000)
OBJECTIVES We sought to determine whether abciximab therapy at the time of percutaneous coronary intervention (PCI) would favorably affect one-year mortality in patients with diabetes. BACKGROUND Diabetics are known to have increased late mortality following PCI. METHODS Data from three placebo-controlled trials of PCI, EPIC, EPILOG, and EPISTENT, were pooled. The one-year mortality rate for patients with a clinical diagnosis of diabetes mellitus was compared with the rate for nondiabetic patients treated with either abciximab or placebo. RESULTS In the 1,462 diabetic patients, abciximab decreased the mortality from 4.5% to 2.5%, p = 0.031, and in the 5,072 nondiabetic patients, from 2.6% to 1.9%, p = 0.099. In patients with the clinical syndrome of insulin resistance—defined as diabetes, hypertension, and obesity—mortality was reduced by abciximab treatment from 5.1% to 2.3%, p = 0.044. The beneficial reduction in mortality with abciximab use in diabetics classified as insulin-requiring was from 8.1% to 4.2%, p = 0.073. Mortality in diabetics who underwent multivessel intervention was reduced from 7.7% to 0.9% with use of abciximab, p = 0.018. In a Cox proportional hazards survival model, the risk ratio for mortality with abciximab use compared with placebo was 0.642 (95% confidence interval 0.458–0.900, p = 0.010). CONCLUSIONS Abciximab decreases the mortality of diabetic patients to the level of placebo-treated nondiabetic patients. This beneficial effect is noteworthy in those diabetic patients who are also hypertensive and obese and in diabetics undergoing multivessel intervention. Besides its potential role in reducing repeat intervention for stented diabetic patients, abciximab therapy should be strongly considered in diabetic patients undergoing PCI to improve their survival.